Conjugated Polymer Amplified Far‐Red/Near‐Infrared Fluorescence from Nanoparticles with Aggregation‐Induced Emission Characteristics for Targeted In Vivo Imaging. Issue 3 (26th November 2012) - Ding, Dan; Li, Kai; Qin, Wei; Zhan, Ruoyu; Hu, Yong; Liu, Jianzhao; Tang, Ben Zhong; Liu, Bin
Abstract Fluorescence‐amplified far‐red/near‐infrared (FR/NIR) nanoparticles (NPs) are synthesized by co‐encapsulation of conjugated polymer donor (poly[9, 9‐bis(2‐(2‐(2‐methoxyethoxy)ethoxy)ethyl)fluorenyldivinylene]; PFV) and a fluorogen acceptor (2‐(2, 6‐bis((E)‐4‐(phenyl(4′‐(1, 2, 2‐triphenylvinyl)‐[1, 1′‐biphenyl]‐4‐yl)amino)styryl)‐4H‐pyran‐4‐ylidene)malononitrile; TPE‐TPA‐DCM) with aggregation‐induced emission (AIE) characteristics using biocompatible bovine serum albumin (BSA) as the encapsulation matrix. The good spectral overlap and close proximity between PFV and TPE‐TPA‐DCM in BSA NPs result in a 5.3‐fold amplified TPE‐TPA‐DCM emission signal via fluorescence resonance energy transfer (FRET). The obtained PFV/TPE‐TPA‐DCM co‐loaded BSA NPs are spherical in shape with a large Stokes shift of ∼223 nm and low cytotoxicity. The BSA matrix allows further functionalization with arginine‐glycine‐aspartic acid (RGD) peptide to yield fluorescent probes for specific recognition of integrin receptor‐overexpressed cancer cells. The advantage of PFV amplified FR/NIR signal from TPE‐TPA‐DCM is further demonstrated in cellular and in vivo imaging using HT‐29 colon cancer cells and a murine hepatoma H22 tumor‐bearing mouse model, respectively. The high FR/NIR fluorescence and specific cancer targeting ability by RGD surface functionalization make the PFV/TPE‐TPA‐DCM co‐loaded BSA‐RGD NPs a unique FR/NIR fluorescent probe for cellular imaging and in vivo tumor diagnosis in a high contrast and selective manner.